Vth shift in single-layer graphene field-effect transistors and its correlation with Raman inspection - Wei, J. (2013)
Raman measurement is carried out to understand Vth shift in single-layer graphene field-effect transistors (GFETs). The G (2D) peak shift in Raman spectra is correlated to the corresponding ΔVth during stress and recovery phases. A blue (red) shift of G and 2D peaks is seen during stress (recovery) phase, indicating the corresponding trapping (detrapping) effects in the graphene device. It is interesting to note that, after forming gas annealing (H2/Ar), the defects can be generated in graphene (evidenced by D peak of Raman spectra), leading to the increased ΔVth for both negative bias temperature instability and positive bias temperature instability in single-layer GFETs.